VERIFICATION OF PHYSICAL CAPACITIES CORRELATIONS IN GIRL VOLLEYBALL PRACTITIONERS. (Fiep Bulletin - online, 2011)
The volleyball popularization, a complex modality that demands from its practitioners a variety of physical capacities, contributes for the increase of the adolescents in specialized training. Nevertheless, the literature is in need of normative data for this population, which contributes for the training processes, according with the sportive modality performed. This study aimed to evaluate and to correlate the capacities of attack vertical jump (AVJ) and of blockage (BVJ), anaerobic power (AnP) and maximum oxygen consumption (VO2 max) of adolescents submitted to the sportive initiation in the modality of volleyball. 25 girls, with age between 12 and 14 years old, from a volleyball training center took part in this study. The tests used were the vertical jump, 40 seconds and Cooper. The program Bioestatic 3.0 described the statistical analysis, where we used the Pearson correlation with a significance value (p
Keywords: adolescents; physical capacities; volleyball